Industry 5.0: Moving Towards Inclusive and Sustainable Industrialization - Verma, Ravish Chandra; Sunidhi, (Nepalese Journal of Management Science and Research, 2024)
The entire globe is going through a technological golden age. The use of modern technologies in various fields of business has become very popular and common. Innovative methods are being developed in every aspect of production, distribution, finance, and marketing. The gradual development of the industrial revolution continues and it is in its fourth and fifth phases. The foundation of Industry 4.0 was laid down by the concept of the smart factory for production, and machine learning, with huge data storage systems and this revolution is connected with the cyber-physical production system. The collaboration of humans with machines elevated in Industry 4.0 but the social angle of this revolution has been ignored. Industry 4.0 was technology-driven so people noticed that their job opportunities were getting replaced with machine work and so there were many cut-offs in the service sector. Industry 5.0 is both technology-driven and value-driven, and in this revolution, humans will also get better opportunities and tasks to show their efficiency and creative skills and to overcome those insecurities in Industry 4.0, the main focus of this evolution was to use the creativity of human experts working together with efficient, intelligent and accurate machines. This paper tries to emphasize inclusive and sustainable industrialization through the Industrial Revolution.